CONSISTENT ATMOSPHERIC AND OCEANIC EXCITATION OF THE EARTH'S FREE POLAR MOTION - Seitz F.; Stuck J.; Thomas M. (My University, 2004)
Earth orientation parameters as observed by space-geodetic techniques show a broad spectrum of frequencies. Many efforts have been made to relate spectral peaks to geophysical processes, such as atmospheric or oceanic variations. However, the mechanisms of excitation of some typical oscillations are still unclear. In order to gain insight into the rotational dynamics of the Earth, the non-linear gyroscopic Dynamic Model for Earth Rotation and Gravity (DyMEG) has been developed at DGFI (Deutsches Geodätisches Forschungsinstitut). The present paper studies the superposed effect of atmospheric and oceanic excitation on the free rotation of a viscoelastic gyro. In contrast to former investigations, period and damping of the Earth's free wobble (Chandler wobble) are generated by the gyro from geometrical and rheological parameters. Numerical results for polar motion in the time domain demonstrate that DyMEG creates a damped oscillation in absence of geophysical and gravitational excitations. Damping vanishes when atmospheric and oceanic angular momentum is regarded. Simulated polar motion for the period from 1975 to 1994 forced by consistent atmospheric and oceanic angular momentum shows significant correlation with geodetic observations, which indicates that the free gyroscopic model DyMEG is able to reproduce realistic variations of the Earth's rotation. Spectral analyses of both atmospheric and oceanic excitations give no hint for increased power in the Chandler frequency band as it was stated for the maintenance of the Chandler wobble in recent research studies. Thus, stochastic signals in the climate dynamics as caused by both the weather and oceanic mass redistributions are found to be a sufficient source to maintain the amplitude of the Earth's free wobble by resonant interaction.
Keywords: atmosphere; Earth’s rotation; oceans; polar motion; wobble